Development of a Problem-Based E-Module on Particle Motion Dynamics to Improve Physics Problem-Solving Skills Using Flip - Anggri Wijaya, Silvia; Lumbu, Albert; Pamangin, Wilda Wijayani; Bisyahri, Adam (Kasuari: Physics Education Journal (KPEJ), 2025)
This study aims to examine the feasibility of an e-module on particle dynamics developed using Flip PDF Professional and to analyze the improvement of students’ physics problem-solving skills. The research subjects were physics education students at Cenderawasih University The research employed an R&D method with the 4D model. The data analysis technique for assessing product feasibility used a standardized scale. The e-module evaluation was conducted through expert validation, and the results were analyzed quantitatively. Furthermore, to determine the impact of the developed e-module on students’ physics problem-solving abilities, an N-gain analysis was applied. To obtain scores for the research variables, a physics problem-solving skills test instrument was used. The validation results showed that the e-module was categorized as very good by media experts (average score 38.5) and material experts (average score 41.5). Field testing indicated that the improvement in problem-solving skills was in the moderate  category, with an N-gain value of 0.69 and an average post-test score of 80.20. Based on the findings obtained, this e-module has been proven to be feasible to function as one of the optional teaching materials in physics lessons.